The 40S ribosomal protein SA-2 inhibits citrus yellow vein clearing virus infection in Eureka lemon via activating jasmonic acid and photosynthetic pathways - Ping Liao; Mengyang Huangfu; Dongdong Ding; Xue Dan; Li Chen; Binghai Lou; Yan Zhou (Phytopathology Research, 2025)
Abstract The 40S ribosomal protein SA (RPSA) functions as an important regulatory factor in plant resistance to abiotic stresses. However, the role of RPSA in response to plant virus infection is poorly understood. Citrus yellow vein clearing virus (CYVCV) has a significantly negative impact on citrus production, and its coat protein (CP) is involved in viral pathogenicity. In this study, we revealed the interaction of CP with Eureka lemon 40S RPSA (ClRPSA-2) in the nucleus, membrane, and endoplasmic reticulum of Nicotiana benthamiana. Further experiments demonstrated that the ClRPSA-2 N-terminal conserved region (amino acids 22—122) was involved in the interaction with CP, and the ClRPSA-2 expression in young Eureka lemon leaves significantly reduced. Transient expression of ClRPSA-2 triggered the expression of jasmonic acid (JA), photosynthetic pathway- and resistance-related genes, as well as increased the JA content and maximum photochemical efficiency (Fv/Fm) in lemon. Furthermore, ClRPSA-2 negatively regulated CYVCV resistance in plants, which induced resistance to other citrus viruses. These findings enhance our understanding of the interaction between CYVCV and citrus plants and provide a basis for future research on resistance breeding of citrus.